Verbs and gender: the hidden agenda of a multicultural society - Mohd Faeiz Ikram bin Mohd Jasmani,; Mohamad Subakir Mohd Yasin,; Bahiyah Abd Hamid,; Yuen, Chee Keong; Zarina Othman,; Azhar Jaludin, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This study explores the issue of gender inequality displayed in action verbs found in English language secondary school textbooks using the Hidden Curriculum Theory. The two aspects of hidden curriculum are the frequency imbalance, i.e., male occurrences are more than female, and gender stereotyping based on roles, i.e., masculine against feminine activities. This study used both quantitative and qualitative methods for collecting data. Wordsmith Tools 4.0 (WST) was used to analyse five categories of action verbs: activity verbs, process verbs, verbs of bodily sensation, transitional event verbs, and momentary verbs. The concordance tool from the WST was used to tabulate occurrences based on gender portrayals. School teachers who taught English at secondary schools were also interviewed to validate the findings and link them to the theoretical framework used. The findings reveal gender inequality is evident in these textbooks.